Odontoma associated with unerupted primary tooth in primary dentition – Three cases. Issue 1 (April 2018) - Takashima, Yukiko; Morikawa, Yuko; Takagi, Atsushi; Matsumi, Yuki; Matsumura, Tatsushi; Iida, Seiji; Naka, Shuhei; Matsumoto-Nakano, Michiyo
Abstract: Odontomas are generally encountered in permanent dentition and rarely seen in primary dentition. These lesions are regarded as essentially benign, though they often cause disturbances in eruption of the associated tooth. We present clinical findings and management of 3 cases of odontomas that occurred in primary dentition, including a 3-year-old girl referred for examination of an unerupted left upper primary canine, a 6-year-old boy with an unerupted left lower second primary molar, and a 5-year-old girl who was presented with an unerupted right upper second primary molar. In all cases, periapical and panoramic radiography revealed a radio-opaque mass surrounded by a narrow radiolucent space located above the crown of the unerupted tooth. Each was diagnosed as a compound odontoma interfering with eruption of a primary tooth and surgical removal was performed under general anesthesia for all patients, with the final diagnosis based on histological findings. Following surgery, the primary canine in Case 1 spontaneously erupted, while a space maintenance appliance was applied in Case 2 and 3. It is important to recognize that an odontoma can appear in primary dentition, though the incidence is quite low. Early detection and removal of an odontoma associated with an impacted primary tooth is necessary for optimal dentition.